Neonatal Acute Kidney Injury: A Survey of Neonatologists' and Nephrologists' Perceptions and Practice Management - Kent, A. L.; Charlton, J. R.; Guillet, R.; Gist, K. M.; Hanna, M.; El Samra, A.; Fletcher, J.; Selewski, D. T.; Mammen, C. (American Journal of Perinatology, 2018)
Background Neonatal acute kidney injury (AKI) occurs in 40 to 70% of critically ill neonatal intensive care admissions. This study explored the differences in perceptions and practice variations among neonatologists and pediatric nephrologists in diagnostic criteria, management, and follow-up of neonatal AKI.Methods A survey weblink was emailed to nephrologists and neonatologists in Australia, Canada, New Zealand, India, and the United States. Questions consisted of demographic and unit practices, three clinical scenarios assessing awareness of definitions of neonatal AKI, knowledge, management, and follow-up practices.Results Many knowledge gaps among neonatologists, and to a lesser extent, pediatric nephrologists were identified. Neonatologists were less likely to use categorical definitions of neonatal AKI (p < 0.00001) or diagnose stage 1 AKI (p < 0.00001) than pediatric nephrologists. Guidelines for creatinine monitoring for nephrotoxic medications were reported by 34% (aminoglycosides) and 62% (indomethacin) of respondents. Nephrologists were more likely to consider follow-up after AKI than neonatologists (p < 0.00001). Also, 92 and 86% of neonatologists and nephrologists, respectively, reported no standardization or infrastructure for long-term renal follow-up.Conclusion Neonatal AKI is underappreciated, particularly among neonatologists. A lack of evidence on neonatal AKI contributes to this variation in response. Therefore, dissemination of current knowledge and areas for research should be the priority.
Keywords: neonatologist; pediatric nephrologist; neonatal acute kidney injury; survey